2009
DOI: 10.1007/s12640-009-9140-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuromelanin Activates Microglia and Induces Degeneration of Dopaminergic Neurons: Implications for Progression of Parkinson’s Disease

Abstract: In Parkinson's disease (PD), there is a progressive loss of neuromelanin (NM)-containing dopamine (DA) neurons in substantia nigra (SN) which is associated with microgliosis and presence of extracellular NM. Herein, we have investigated the interplay between microglia and human NM on the degeneration of SN dopaminergic neurons. Although NM particles are phagocytised and degraded by microglia within minutes in vitro, extracellular NM particles induce microglial activation and ensuing production of superoxide, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
192
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 227 publications
(201 citation statements)
references
References 32 publications
7
192
0
2
Order By: Relevance
“…Accordingly, recent studies using genetic deletion of gp91 phox have shown that microglial activation and NADPH-oxidase-derived free radicals play major roles in the toxicity of a variety of compounds leading to dopaminergic neuronal death (75,76). Apocynin has been used effectively to inhibit neurotoxicity for 6-OHDA (77), MPTP/MPP + (75,78), neuromelanin (79) and environmental neurotoxins such as paraquat (80,81), rotenone (82) and formyl-methionyl-leucyl-phenylalanine (83) in vitro with dopaminergic neurons, neuron-glia co-cultures or slice culture preparations. Most importantly, apocynin is also beneficial when used in vivo in different animal models of PD; preadministration of apocynin protects against paraquat-induced dopaminergic cell death in mice (80) and 6-OHDA-induced neurodegeneration in rats (84).…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Accordingly, recent studies using genetic deletion of gp91 phox have shown that microglial activation and NADPH-oxidase-derived free radicals play major roles in the toxicity of a variety of compounds leading to dopaminergic neuronal death (75,76). Apocynin has been used effectively to inhibit neurotoxicity for 6-OHDA (77), MPTP/MPP + (75,78), neuromelanin (79) and environmental neurotoxins such as paraquat (80,81), rotenone (82) and formyl-methionyl-leucyl-phenylalanine (83) in vitro with dopaminergic neurons, neuron-glia co-cultures or slice culture preparations. Most importantly, apocynin is also beneficial when used in vivo in different animal models of PD; preadministration of apocynin protects against paraquat-induced dopaminergic cell death in mice (80) and 6-OHDA-induced neurodegeneration in rats (84).…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…In neuronal/glial mixed culture, nanomolar Aβ, which was not directly toxic to neurons but activated microglia, induced neuronal death by microglial phagocytosis [3]. It has been reported also in PD model that microglial phagocytosis might be involved in neuronal loss [48][49][50]. Taken together, the control of microglial phagocytosis might be important for neuronal survival in neurodegenerative diseases and the regulations of TG2 expression and TG enzyme activity might be targets of the mechanism to control microglial phagocytosis.…”
Section: Phagocytosis In Neurodegenerative Diseasesmentioning
confidence: 91%
“…Notably, quantitative susceptibility mapping appears to be more sensitive for iron estimation in the SNpc than R2* transverse relaxivity measurement [120][121][122][123][124]. At the microscopic level, iron deposits in the SNpc are associated with neuromelanin granules in dopaminergic neurons [125], Lewy bodies [32], and activated microglial cells [126]. Enhanced diffuse iron staining is also apparent in the neuropil of the SN [127].…”
Section: Parkinson's and Alzheimer's Diseasesmentioning
confidence: 99%